PREDIKSI NIAT KEPATUHAN PAJAK MENGGUNAKAN EXTENDED THEORY OF PLANNED BEHAVIOR (Survei Wajib Pajak Orang Pribadi di Beberapa Kota di Jawa Tengah) - , Fajar Prabowo; , Prof. Dr. Jogiyanto Hartono, H.M., MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to examine whether an extended theory of planned behavior can explain the factors that affect tax compliance intentions individual taxpayer in several cities in Central Java. This research combines several constructs from previous research and use descriptive and injunctive norms construct in place of subjective norm to measure the perceived social pressure. Data analysis and hypothesis testing using the Partial Least Square because Partial Least Square is a reliable tool to test the model predictions. Hypothesis testing results show that perception of fairness of the tax system, attitudes towards compliance and injunctive norms have a positive influence on tax compliance intentions, whereas descriptive norms, moral norms and perceived behavioral control no effect on tax compliance intentions. Injunctive norm became the most significant influence construct on tax compliance intentions as indicated by the beta coefficient of 0.273033 and 1.978116 T-statistics. This indicates that the individual taxpayer to behave more realistically in accordance with the SPT report done by most people (other taxpayer in the environment around it). Individual taxpayer seeking to build and maintain social ties with the behaving the best for themselves and their environment and not in conflict with social norms in society.